Drug-Related Problems and Associated Factors in Depressive Disorders: A Systematic Review - Dewi Nurul Aini; Atika Wahyu Puspitasari; Nadia Farhanah Syafhan (Journal of Community Health Provision, 2026)
Depressive disorders are mental health condition marked by a persistent moody mood or loss of pleasure or interest in activities. It is commonly associated with complex treatment regimens and multiple coexisting conditions, which can lead to drug-related problems compromising treatment outcome. This systematic review aimed to identify the types of drug-related problems and factors associated among patients with depressive disorders. The review was conducted following the PRISMA 2020 guidelines, and a comprehensive literature search was conducted in PubMed and Scopus studies published between 2015-2025. The most frequently reported drug-related problems were polypharmacy, drug interactions, adverse drug reactions, medication non adherence, inappropriate prescribing, and undertreatment. Factor associated with the occurance of drug-related problems included female sex, low educational level, unemployment, disease severity, psychiatric comorbidities, polypharmacy, prolonged treatment duration, limited acces to healthcare services, and socioeconomic constaints. Polypharmacy was the most consistently reported factor across studies. In conclusion, drug-related problems are common among patients with depressive disorders and are influenced by multiple patient disease, medication, and healthcare-related factors. Regular medication review and monitoring are essential to improve medication safety and optimize treatment outcomes.